Whose reality Counts? putting the first last - Chambers, Robert (Warwickshire Practical Action Publishing, 2009)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.
Includes bibliographies and index
Keywords: Development